Dampak Bencana Gempabumi dan Tsunami Pesisir Lere Kota Palu - Fauzi, Mohammad; Mussadun, Mussadun (Jurnal Pembangunan Wilayah dan Kota, 2021)
Palu City is one of the active seismic areas in Indonesia because it is passed through a fault segmentation that has the potential to generate strong earthquakes, namely the Palu-Koro Fault which extends from Palu to the South and Southeast. The earthquake and tsunami that occurred on September 28 2018 impacted along the coast of Palu City, especially in the Lere Coast of Palu City. Departing from these problems, this study aims to identify and analyze the impact of the earthquake and tsunami disaster on the Lere Coast of Palu City with the hope of providing information on economic, social and environmental losses. The method used in this research is qualitative descriptive obtained from interviews and lethargy studies, which are formatted into verbatim form, displayed in figures and tables. The results showed that the earthquake and tsunami disaster had an impact on the damage to assets in the form of residents' houses, commercial buildings and infrastructure; loss of business and loss of livelihood for traders and fishermen; damage to people in the form of death, injury; service disruption in the form of food, fuel supply, health, welfare, finance, care and medical services, loss of strength in the form of trauma, and damage to water, air and land.